Mucinous adenocarcinoma within an anal fistula in a patient with Crohn’s disease - Riaza Montes, María; Olabarria, Unai De Andrés; Bergara, Izaskun Badiola; Porras, Vicente Portugal; Aguirre, Francisco Javier Ibáñez (International Surgery Journal, 2019)
Anal mucinous adenocarcinoma is a rare entity, representing approximately 5-11% of all anal cancers. Sometimes it is associated with chronic inflammation of long-standing anal fistula as it may occur in patients with Crohn’s disease. In this case, cancer usually goes unnoticed owing to the inflammatory disease; therefore, a degree of uncertainty surrounds initially the diagnosis. We report a case of a 62-year-old man with A2 L3 B3p Crohn’s disease who also presents a perianal mucinous pseudocyst that is removed. Histological examination reveals a mucinous pseudocyst. At the two-year follow-up, we observe the recurrence of the cyst within an anal fistula. Scheduled non-oncologic surgery is performed with resection of the cyst and tutoring of the fistula with seton. Histological examination reveals mucinous adenocarcinoma. With no evidence of metastasis in the extension study, the patient is subjected to radical surgery with abdominoperineal resection. After 3 years and 11 months, a follow-up is carried out and there is no evidence of recurrence or distant metastasis. Mucinous adenocarcinoma within an anal fistula is a challenge in its diagnosis and its treatment due to the anecdotal nature of the cases. Given the high local risk of recurrence, radical surgery is recommended, occasionally associating neoadjuvant chemoradiotherapy if the neoplasm is locally advanced.